World Food Trends and the Future of Food (Volume 6) - Nobile, Marianna (2015)
Following the Milan Universal Exposition, the scientific debate about food and nutrition has gained particular attention in 2015. As a result, this volume focuses on issues related to food safety, consumption, research and technology. Within the Hórisma project, funded by the University of Milano-Bicocca and the University of Milan, four young scholars investigated the possible developments of food production and consumption from different perspectives through a critical analysis on food trends in the international scenario. The main theme that links all the essays collected in this book is the belief that stimulating dialogue among different disciplines, as well as promoting an integrated and multidisciplinary approach, is crucial to face all the issues concerning food and its connections to law, technology, society, and science.